Spontaneous resolution of non-occlusive mesenteric ischemia in the setting of hemodialysis: a case report - Choudhury, Nishat; Choudhury, Noshin; Jung, Alex (International Surgery Journal, 2025)
Non-occlusive mesenteric ischemia (NOMI) is a rare yet serious cause of acute abdominal pain, particularly affecting critically ill and dialysis-dependent patients. Unlike occlusive mesenteric ischemia, NOMI results from mesenteric hypoperfusion without vascular obstruction, making early diagnosis challenging. We report a case of a 46-year-old female with end-stage renal disease (ESRD) on hemodialysis who presented with severe abdominal pain and hypertensive emergency following dialysis. Initial imaging revealed portal venous gas (PVG) without evidence of bowel obstruction or bowel ischemia. Despite intractable pain, her condition improved with supportive care, including blood pressure management, without the need for invasive intervention. A repeat CT scan showed resolution of PVG, correlating with clinical improvement. Hemodialysis-associated hypotension is a known risk factor for NOMI due to transient mesenteric hypoperfusion. This case highlights the role of blood pressure fluctuations in NOMI’s pathophysiology, with post-dialysis hypertension potentially aiding in recovery. Additionally, the transient presence of PVG on imaging, which resolved alongside symptom improvement, suggests its utility in diagnosing and monitoring NOMI. This case underscores the importance of recognizing NOMI in dialysis patients with abdominal pain, close blood pressure monitoring, and utilizing serial CT imaging for non-invasive disease management. Our findings suggest that in select patients with rapid clinical recovery, PVG disappearance may serve as a marker for NOMI resolution, potentially avoiding unnecessary laparotomy.